Clear cell injury associated with reduced expression of carbonic anhydrase II in eccrine glands consistently occurs in patients with acquired idiopathic generalized anhidrosis. Issue 4 (16th January 2021) - Sano, Kenji; Asahina, Masato; Uehara, Takeshi; Araki, Nobuyuki; Yamanaka, Yoshitaka; Matsumoto, Kazuhiko; Okuyama, Ryuhei
Abstract: Acquired idiopathic generalized anhidrosis (AIGA) is characterized by anhidrosis/hypohidrosis without other autonomic and neurological dysfunctions. It has been believed that AIGA patients usually present no significant morphological alterations in the secretory portion of eccrine glands consisting of clear, dark and myoepithelial cells. However, we have recently revealed morphological damage of eccrine glands in AIGA patients by immunohistochemistry. Moreover, inhibitory side‐effects against carbonic anhydrase II (CA II) by the antiepileptic reagent topiramate have been reported to cause heat intolerance mimicking AIGA. To determine the precise morphological changes and CA II expression in eccrine glands of AIGA patients, electron microscopic observation and immunohistochemistry were applied to skin of both anhidrotic (non‐sweating) and normohidrotic (sweating‐preserved) sites, taken from each patient clinically diagnosed with AIGA. We found consistent clear cell injury in eccrine glands in anhidrotic skin samples of AIGA patients. Electron micrographs demonstrated edematous, swollen and destructive damage in clear cells of eccrine glands from non‐sweating areas of almost all AIGA patients. Immunohistochemically, clear cells showed reduced CA II expression that was heterogeneously distributed in non‐sweating skin. Some areas showed almost complete loss of CA II expression in spite of preserved dark cells, and others showed mild or moderate loss of it. Selective destruction of clear cells resulting in heterogenous atrophy in AIGA patients may be important to elucidate its etiology.